Socio-economic factors and child health status in Ghana - Immurana, Mustapha; Urmi, Arabi (International Journal of Health, 2017)
Ghana’s under-five mortality rate far exceeds the Sustainable Development Goal (SDG) 3.2 Target of 25 deaths per thousand live births by 2030. Therefore to improve upon the situation, it is imperative that the factors which determine the health status of children are investigated. This study therefore used data from the 2014 Ghana Demographic and Health Survey to investigate the socio-economic determinants of child health status in Ghana by employing the binary probit model. The study revealed that, Ewe, Grusi, Muslim and Christian children, children from urban areas, Greater Accra, Northern, Ashanti, Upper east, Eastern and Central regions, were more probable to contract cough. Also children with uneducated mothers, those whose mothers had uneducated partners as well as those whose mothers had no health insurance were revealed to be more likely to be anaemic. Further, male children and children from non-wealthy households were revealed to be more likely to have suffered diarrhoea, fever and anaemia. Also children with employed mothers and those with mothers with big distance challenges to seek care were found to be more likely to have fever. These findings, point out the essence of socio-economic factors to child health outcomes and hence the need to be given attention in child health survival interventions in Ghana.